2017
DOI: 10.1002/ldr.2729
|View full text |Cite
|
Sign up to set email alerts
|

Using OSL Measurements to Decipher Soil History in Archaeological Terraces, Judean Highlands, Israel

Abstract: Archaeological terraces are a prominent feature of the agricultural sphere in hilly landscape throughout the Mediterranean, and dating of these simply built features is of utmost importance. Excavations and optically stimulated luminescence (OSL) dating of the soil fill of terraces were previously carried out on Mt. Eitan, the Judean Highlands, Israel. Archaeological surveys showed that Mt. Eitan was almost continuously settled from the Middle Bronze Age until modern times. However, OSL dating showed that all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…Our study is compatible with previous research showing that the archaeological landscape history of Israel is based on the interaction between human activities and the physical structure (Ackermann, 2007;Ackermann et al, 2017;Aviam, 2004;Ben-David, 2005;Davidovich et al, 2012;Porat et al, 2017;among others). On the basis of our examination of the distribution of burial caves relative to the geological formation, we conclude that there is a strong correlation between rock type, location, and tomb frequency.…”
Section: Correlation Between Rock Type Location and Frequencysupporting
confidence: 92%
“…Our study is compatible with previous research showing that the archaeological landscape history of Israel is based on the interaction between human activities and the physical structure (Ackermann, 2007;Ackermann et al, 2017;Aviam, 2004;Ben-David, 2005;Davidovich et al, 2012;Porat et al, 2017;among others). On the basis of our examination of the distribution of burial caves relative to the geological formation, we conclude that there is a strong correlation between rock type, location, and tomb frequency.…”
Section: Correlation Between Rock Type Location and Frequencysupporting
confidence: 92%
“…Furthermore, terraces abandoned for a short time (less than 25–30 years) resulted in the most hazardous land use class, showing erosion rates that were approximately 2‐ and 3‐times higher than terraced slopes abandoned a long time ago (more than 25–30 years). Porat, Davidovich, Avni, Avni, and Gadot () presented a study on optically stimulated luminescence measurements to decipher soil history for archaeological terraces located in the Judean Highlands (Israel). Archaeological surveys showed that Mt.…”
Section: Overview Of the Papers In This Special Issuementioning
confidence: 99%
“…But buried soil horizons are often missing, bulk samples tend to yield overestimates of ages due to the presence of older carbon fractions in the environment, and interpretation can also be complicated by problems of 'old wood' (Puy et al 2016;Ferro-Vasquez et al 2019). Luminescence dating, which can be used to determine when certain minerals were last exposed to light or were heated, has also been used to date terrace soils and constructional fills (Davidovich et al 2012;Porat et al 2018). Nevertheless, luminescence and radiocarbon dating both have an Figure 1.…”
Section: Introductionmentioning
confidence: 99%